"Will she live a long happy life?" Parents' concerns for their children with Fontan circulation. (March 2018) - du Plessis, Karin; Peters, Rebecca; King, Ingrid; Robertson, Kirsty; Mackley, Jonathan; Maree, Rachel; Stanley, Tracy; Pickford, Louise; Rose, Brian; Orchard, Matthew; Stewart, Helen; d'Udekem, Yves
Abstract: Background: Families of children at the worst end of the congenital heart disease endure a significant burden which is often not clearly delineated in the clinical literature. We examined the greatest concerns of parents whose children have a Fontan circulation. Methods: Parents ( N  = 107) of children in the Australian and New Zealand Fontan Registry completed online surveys with open-ended and closed questions. A qualitative method approach incorporating thematic analyses was used. Results: The greatest concerns for parents of a child with a Fontan circulation were centered on fear of death for their child and psychosocial well-being, followed by lesser themes around anti-coagulation use, pregnancy and financial burdens. Conclusions: Fear of death and the psychological well-being of their children were the main parental concerns. It highlights the need to clearly communicate information on outcomes to families, and the need for family-focused psychological interventions to improve the psychosocial functioning of both parents and young people. Highlights: Fontan parents' greatest concern for their child is fear of death and well-being. Clear communication around outcomes could help alleviate these fears. It highlights the need for psychological support for parents and young people.